Analisis Kerusakan Lingkungan Akibat Industri di Permukiman Warga Desa Karangrejo Kediri - Anurrohmah, Silfia; Sudarti, Sudarti (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2021)
In the modern era like this there is a lot of development, industry everywhere, and technological advances, especially in industry. Industry is a key to economic growth, the growth of people's incomes around the industry and the growth of development. In addition, there is an impact of industrial activities on the environment, especially when the industry is around the settlements of residents. The purpose of this study is to find out the environmental damage caused by industry in the settlements of Karangrejo Kediri villagers. Where in the village area there are many industries that are close to or located in the settlements of residents. The research method used is a descriptive method with data obtained from questionnaire results and observations. The results of the study showed the presence of air pollution, water pollution, noise pollution, the reduction of green land, roads that look hollow and the number of vehicles passing by. The conclusion needs personal awareness and more attention to maintain the environment and maintain the environment so as not to be damaged and favor the villagers.